STUDI ANALISA GANGGUAN HUBUNG SINGKAT 1 FASA KE TANAH PADA SUTT 150 KV UNTUK SETTING RELAY OCR (APLIKASI GI PIP – PAUH LIMO - Amira Amira; Asnal Effendi (Situs resmi ITP Press, 2014)
Short circuit was the common disturbance on a power system that increased the current flow causing damage any equipment without a proper protection system. This research was study 1-phase shortcircuit to ground at 10% until 100% transmission length disturbance point and calculate Over Current Relay (OCR) protection setting base on disturbance current occurred. The calculation performed using manual and Matlab software, case study on GI PIP – Pauh Limo, a 22.7 km transmission length. Base on calculation result, it was found that if the disturbance getting closer to the source (disturbance point 10% of transmission length), than disturbance current increased until 147.7758 A. While the disturbance gettingaway from the source (disturbance point 100%), than disturbance current decreased until 147.3853 A. As toprotect the power transmission line from 1-phase short circuit to ground, the 0,65 s OCR setting time should be used at input and output transmission line